Self-help : with illustrations of character and conduct - Smiles, Samuel, 1812-1904 (Cambridge : Cambridge University Press, 2014)
One of the most popular and prolific writers during the Victorian age, Samuel Smiles (1812-1904) emphasised individual responsibility in the pursuit of personal and social improvement. Among other titles, his acclaimed Lives of the Engineers (1861-2) and insightful Autobiography (1905) are also reissued in the Cambridge Library Collection. He is best known, however, for the present work. First published in 1859, it sold 20,000 copies in its first year, more than a quarter of a million by 1905, and was widely translated. Using hundreds of biographical examples, ranging from George Stephenson to Josiah Wedgwood, Smiles champions the virtues of hard work, perseverance and character in achieving success. While these values appealed to a large readership in the book's heyday, later critics saw the work as promoting a form of selfish materialism. However interpreted, this remains a crucial text for those fascinated by the Victorian drive for self-improvement.
Introduction -- 1. Self-help, national and individual -- 2. Leaders of industry, inventors and producers -- 3. Application and perseverance -- 4. Helps and opportunities -- 5. Workers in art -- 6. Industry and the English peerage -- 7. Energy and courage -- 8. Business qualities -- 9. Money, use and abuse -- 10. Self-culture -- 11. Facilities and difficulties -- 12. Example -- Character - the true gentleman -- Index.
Originally published: London : John Murray, 1859.
Keywords: Conduct of life